Improving the training process of highly skilled bodybuilders in the preparatory period, general preparatory phase - Тихорський Олександр Анатолійович (Olexandr Tyhorskyy) (Slobozhanskyi Herald of Science and Sport, 2015)
Purpose: to improve the method of training highly skilled bodybuilders. Material and Methods: the study involved eight highly skilled athletes, members of the team of Ukraine on bodybuilding. Results: comparative characteristics of the most commonly used methods of training process in bodybuilding. Developed and substantiated the optimal method of training highly skilled bodybuilders during the general preparatory phase of the preparatory period, which can increase body weight through muscle athletes component. Conclusions: dynamic load factor to raise the intensity of training loads allows orientation help to increase volumes shoulder muscles